Analisis Kadar Vitamin C pada Selai Buah Naga Merah (Hylocereus polyrhizus) dengan Penambahan Ekstrak Daun Kelor (Moringa oleifera) sebagai Sumber Antioksidan - Rida Astria; Salsabila Ardelia; Saepudin Rahmatullah (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2026)
Vitamin C is a water-soluble vitamin essential for the body and is known as a powerful antioxidant capable of reducing free radicals and protecting cells from oxidative damage. However, vitamin C is very easily degraded, so its levels in food often decrease during processing and storage. This study aims to analyze vitamin C levels in red dragon fruit (Hylocereus polyrhizus) jam, with and without the addition of moringa leaf extract (Moringa oleifera), using the iodometric titration method. The results showed that the vitamin C level in the standard jam was 38.04 mg/100 g, while the jam with moringa leaf extract decreased to 20.43 mg/100 g. This decrease was influenced by the degradation of ascorbic acid due to heat, oxidation, the presence of bioactive compounds and metal ions in the moringa extract, and possible matrix interference in the titration analysis. The complexity of the jam’s color and viscosity can also affect the accuracy of the titration endpoint determination. Thus, the addition of moringa leaf extract did not increase vitamin C retention, and a more selective analytical method is recommended for further research.